Tensile adhesion strength of sealants in float glass substrates when exposed to accelerated weathering - Sigui, Walleastein L.
Sealant is a material that has the necessary adhesive and cohesive properties to form a seal. Its wide range of uses extends from foundation system, base floor system, up to the roofing system, all of which constitute to the building envelope. In order to evaluate sealants, accelerated weathering apparatus is be used as it provides faster means of amplifying natural weather conditions like heat, UV radiation, and moisture. For this experiment, the sealants were applied to float glass since this material is widely used in modern building envelope applications. The prepared specimens are cured for 21 days. After curing, samples were weathered using the apparatus with a cycle of 8 hours UV heat exposure, and 4 hours of moisture-heat exposure for a total exposure duration of 1000 hours. The performance of sealants, particularly polybutene, acrylic, silicone, polyurethane, and elastomeric, that undergone accelerated weathering were tested using tensile testing machine for tensile adhesion. The polybutene remained paste-like even after 21-days curing. On the other hand, the acrylic experienced adhesion failure before tensile testing was done. Because of these, only silicone, polyurethane and elastomeric were tested using tensile testing machine. It was found that silicone sealant can best resist the simulation of environmental factors which include moisture, UV exposure and extreme weather temperature. Its appearance, with no obvious changes for the duration of the experiment, add up to it being best fit for use in modern building envelopes that make use of float glass as primary material. If resistance to movement is a major concern, polyurethane could be a better choice for such application.